The role of radiotherapy in the treatment of malignant pleural mesothelioma - possibilities and controversy - Arsenijević Tatjana; Stepanović Aleksandar; Nikitović Marina (Srpski Arhiv za Celokupno Lekarstvo, 2024)
Malignant pleural mesothelioma (MPM) is a rare malignancy with poor prognosis. In recent years, significant progress has been made in the treatment of this disease, including surgical and radiotherapy techniques, systemic therapy, and immunotherapy. Due to the wide range of clinical presentations, a lack of phase-III randomized trials, and heterogeneity in treatment approach, the treatment of MPM remains challenging regardless of available diagnostic and therapeutic guidelines. The limited possibility to avoid critical healthy organs (particularly lungs), overexposure of which can lead to severe, and even fatal, radiation-induced toxicity, makes high-dose radical radiotherapy very demanding. Thus, the majority of patients in the era of conventional radiotherapy were mostly referred to no more than palliative radiotherapy. Technological development in radiotherapy such as respiratory gating, 4D computed tomography, intensity-modulated radiotherapy, volumetric modulated arc therapy, stereotactic techniques, and proton therapy, made a step forward in treating MPM with this modality. Today, MPM radiotherapy can be considered in various indications, alone or in combination with surgery and systemic treatment. However, many questions remain open, and further investigation is needed especially in dose escalation possibility and lung sparing.